Work Accident Risk Analysis Using Hazard Analysis and Operability Study Method - Hidayatul Ulumiya; I Nyoman Dita Pahang Putra (PT. Inovasi Teknologi Komputer, 2024)
One of the construction developments in Indonesia is the Kediri Regency Stadium construction project. In every construction project, it is very important to implement Occupational Safety and Health making it a primary concern. This is to anticipate negative impacts, such as increasing absenteeism rates, decreasing productivity, increasing medical costs, as well as a form of controlling all risks of work accidents in the work environment. This impact causes losses for both workers and contractor companies. Therefore, identification, assessment and analysis must be carried out to be able to control the risk of work accidents. The aim of this research is to identify risk factors for work accidents, assess the risk of work accidents, and control risks in the Kediri Regency Stadium construction project. The research method used is the Hazard Analysis and Operability Study (HAZOP) method. The results of this research were 45 risk factors, 29 of which were valid, and the results obtained were 2 extreme risks, 3 high risks, 17 mederate risks and 7 low risks. Apart from that, according to the risk control hierarchy, there are 3 types of risk control that can be applied in this research.